Elucidating the interaction of CO2 in the giant metal–organic framework MIL-100 through large-scale periodic ab initio modeling - D'Amore, M; Civalleri, B; Bush, IJ; Albanese, E; Ferrabone, M (American Chemical Society, 2019)
In this work, we have tackled the challenging task of the ab initio modeling of a gigantic metal–organic framework (MOF). The structural features of MIL-100(MIII) with different metals (i.e., MIII = Al, Sc, Cr, Fe) and the interaction of CO2 with the unsaturated coordination metal sites were investigated by means of large-scale quantum mechanical calculations with hybrid Hartree–Fock/density functional theory methods augmented with an atom–atom pairwise dispersion correction in a fully periodic approach. In doing this, we took advantage of the high scalability of the massively parallel version of the CRYSTAL code. Overall results are in good agreement with the experiment, in particular for the predicted structures, whereas some discrepancies have been found for adsorption energies in the case of MIL-100(Cr) and MIL-100(Sc). We argue that this is due to a deviation of the ideal model structure of MIL-100 adopted in this work from the actual synthesized material. This is also supported by additional calculations on a MOF with similar adsorption sites and computed data from the literature. Above all, we demonstrate that ab initio modeling of the structure and properties of MOFs can now be performed on very large and complex frameworks.